Perspectives on Inhibiting β-Amyloid Aggregation through Structure-Based Drug Design - Mishra P.; Ayyannan S.R.; Panda G. (My University, 2025)
Targeting β-amyloid (Aβ) remains the most desired strategy in Alzheimer's disease (AD) drug discovery research. Many peptides that specifically target Aβ aggregates are known, encompassing efforts from both industrial and academic research settings. However, in clinical terms, not much success has been gained with peptide research; in turn, small drug-like molecules are already globally recognized as showing promise as an alternate approach. Aβ aggregation inhibitors are the most important part of the multifunctional drug design regimen for treating AD. Unfortunately, rational drug design approaches with small molecules are still in the initial stages. Herein we highlight, update, and elaborate on the structural anatomy of Aβ and known Aβ aggregation inhibitors in hopes of helping to optimize their use in structure-based drug design approaches toward inhibitors with greater specificity. Furthermore, we present the first review of efforts to target a previously uncharacterized region of acetylcholinesterase: the N-terminal 7-20 sub-region, which was experimentally elucidated to participate in Aβ aggregation and deposition. © 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.